2017
DOI: 10.1002/ardp.201700226
|View full text |Cite
|
Sign up to set email alerts
|

6‐Nitroazolo[1,5‐a]pyrimidin‐7(4H)‐ones as Antidiabetic Agents

Abstract: Prevention of the formation of advanced glycation end-products (AGEs) is a reliable approach to achieve control over hyperglycemia and the associated pathogenesis of diabetic vascular complications. In these terms, new synthetic approaches to 6-nitroazolo[1,5-a]pyrimidines have been developed on the basis of the promising antiglycation activity of their structural analogues, such as azolo[5,1-c][1,2,4]triazine-4(1H)-ones. A number of nitroazolopyrimidines were obtained by using nitration, chlorodeoxygenation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…It is known that nitroazolopyrimidines and their derivatives possess useful biological activity. 33,[131][132][133][134][135] In addition, the presence of such an important structural fragment as the nitro group seems to be promising from the point of view of further transformations, for example, in the creation of polycyclic purine-like structures. 136…”
Section: Scheme 50mentioning
confidence: 99%
“…It is known that nitroazolopyrimidines and their derivatives possess useful biological activity. 33,[131][132][133][134][135] In addition, the presence of such an important structural fragment as the nitro group seems to be promising from the point of view of further transformations, for example, in the creation of polycyclic purine-like structures. 136…”
Section: Scheme 50mentioning
confidence: 99%
“…Pyrimidine is a heteroaryl system that consists of nitrogen at the first and third positions. In recent years, pyrimidine has gained focus for its use in many diseases as they have been used as antiviral ( Rashad and Ali, 2006 ; Rashad et al, 2009 ; Perlíková and Hocek, 2017 ; Wang et al, 2018 ), anticancer ( Galmarini et al, 2003 ; Song et al, 2011 ; Perlíková and Hocek, 2017 ), anti-hypertensive ( El-Hamouly et al, 2006 ; Ismail et al, 2006 ), anti-mycobacterial ( Garg et al, 2016 ; Khandazhinskaya et al, 2018 ), anti-microbial ( Okasha et al, 2016 ; Beyzaei et al, 2017 ; Marepu et al, 2018 ), anti-diabetic ( Spasov et al, 2017 ; Fang et al, 2018 ) and anti-inflammatory activities ( Zhang et al, 2017 ; Abdelgawad et al, 2018 ) .…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that this class possesses a wide range of antiviral actions [ 18 , 19 ] and an affinity toward adenosine receptors [ 20 ] that is associated with improved survival in LPS-induced septic shock [ 21 ]. Furthermore, some derivatives of this heterocycle series demonstrated higher antiglycation activity than a reference compound, aminoguanidine, and could be considered candidates for extended studies to produce drugs against complications of diabetes mellitus [ 22 , 23 ]. Additionally, it was shown that nitro-derivatives of this series demonstrate low toxicity [ 17 ], which is uncommon for nitro-compounds.…”
Section: Introductionmentioning
confidence: 99%